WAYS TO DEVELOP THE PERSONALITY TRAITS OF AN “ACTIVE-POSITIVE CHILD” IN PRESCHOOL AGE - Maqsuda Norbosheva (Bright Mind Publishing, 2025)
The article highlights the social-psychological development characteristics of preschool children as communication subjects and explores methods for developing their personality traits. Specifically, it presents scientific research on forming the personality of an "active-positive child" based on the self-expression of 5-6-year-old preschool children as communication subjects.
Keywords: Child, personality, activity, positive, preschool, initiative, communication, awareness, self-awareness, traits, play, adults.